Demographic and developmental factors in peacebuilding program among Yemeni university students - Ali Saleh, Ali Alwainani (2018)
As conflict zones increase around the world, youth continue to be victims of the violence. At the same time, in many countries, peacebuilding (PB) programs that target youth are growing. It is important for young people to be involved in such programs for the future well-being and stability of those countries. Based on this theoretical perspective, this study aims to examine the demographic and developmental factors of participation in PB programs among Yemeni university students. This is a quantitative descriptive study aimed at identifying the relationships between demographic and developmental factors, and participation in PB programs. The targeted population for this study was universities’ students from both public and private institutions in Sana’a, the capital city of Yemen. Seven universities were selected from the list of both public and private universities for the purpose of this study. The applied instruments were modified from structured questionnaire, which answered the study questions and addressed the specific objectives. Questionnaires were distributed to respondents via an online google application and responses were collected from May 2017 to July, 2017. The results indicated that the respondents' age were from 20 to 30 years, whereby the majority aged was from 20 to 25 years (86.80%). The percentage gender distribution of the respondent showed that the majority were males with 84.00% while females constituted only 15.90%. The proportion of female engagement in PB has dependably been lower than that of the males as revealed in this study, of whom 1.10% (1/29) of the female students have high level of participation in PB programs. Even though,workshops and classes identified with PB conducted by universities have been distinguished as vital strides toward accomplishing peace, in this study over half of the respondents stated that their universities do not organize PB workshops. Correlation analyses were conducted for defining the degree of association between the independent and dependent variables. The findings revealed a negative linear correlation between aggression and engagement in PB program. The students’ selfefficacy and self-esteem were positively associated their engagement in PB programs. The overall level of engagement in PB among the sample of youth was moderate. Students' engagement in PB did not vary according to the field of study. Regression analysis showed significant relationships between participation in PB and the demographic and developmental factors. Specifically, the findings revealed that selfefficacy was predictive of participation among youth in Yemeni universities. This study has been one of the first attempts to thoroughly examine demographic and developmental factors in PB in Yemen. The findings shed new light on youth participation in PB programs among Yemeni university students as a conflict area. Although this study is based on a small sample of factors, the findings suggest to examine the other factors that motivate youth to actively participate in such programs. Several questions still remain to be answered.